Electrodes: Ferromagnetic, Folded Electrode Composite as a Soft Interface to the Skin for Long‐Term Electrophysiological Recording (Adv. Funct. Mater. 40/2016). (25th October 2016) - Jang, Kyung‐In; Jung, Han Na; Lee, Jung Woo; Xu, Sheng; Liu, Yu Hao; Ma, Yinji; Jeong, Jae‐Woong; Song, Young Min; Kim, Jeonghyun; Kim, Bong Hoon; Banks, Anthony; Kwak, Jean Won; et al.
Abstract : On page 7281, J. A. Rogers and co‐workers describe a ferromagnetic, folded electrode composite. The image demonstrates the ability of the material to hold a coin magnet through a glass slide with strong magnetic attractive force. The material forms irritation‐free but robust contacts to the skin and forms dimensionally stable geometries, making it promising for long‐term electrophysiological monitoring.